MOBILISASI DINI PADA IBU POST SECTIO CAESAREA DENGAN METODE ERACS DI RSNU BANYUWANGI - Widi Astuti, Wuri; Mustofa, linda Andri (STIKES dan AKZI Karya Husada Kediri, 2026)
The Enhanced Recovery After Cesarean Section (ERACS) method is designed to accelerate maternal recovery after cesarean delivery through several interventions, including early mobilization. Early mobilization plays an important role in preventing postoperative complications and improving maternal physical recovery during the postpartum period. This study aimed to describe early mobilization among post–cesarean section mothers who underwent the ERACS method at RSNU Banyuwangi. This study employed a descriptive observational design. The population consisted of postpartum mothers on day 1–2 after cesarean section with the ERACS method at RSNU Banyuwangi. Data were collected from October 3 to November 3, 2024, using a total sampling technique involving 53 respondents. Data were analyzed using univariate analysis and presented as frequency distributions. The results showed that most respondents performed early mobilization rapidly, with 42 respondents (79.2%), while 11 respondents (20.8%) performed early mobilization slowly. In conclusion, the majority of post–cesarean section mothers with the ERACS method at RSNU Banyuwangi achieved rapid early mobilization. The implementation of ERACS contributes positively to faster postoperative recovery. Continuous education and assistance from healthcare providers are needed to optimize early mobilization and prevent postoperative complications.